VLSI Design A Practical Guide for FPGA and ASIC Implementations - Chandrasetty, Vikram Arkalgud (2011)
This book provides insight into the practical design of VLSI circuits. It is aimed at novice VLSI designers and other enthusiasts who would like to understand VLSI design flows. Coverage includes key concepts in CMOS digital design, design of DSP and communication blocks on FPGAs, ASIC front end and physical design, and analog and mixed signal design. The approach is designed to focus on practical implementation of key elements of the VLSI design process, in order to make the topic accessible to novices. The design concepts are demonstrated using software from Mathworks, Xilinx, Mentor Graphics, Synopsys and Cadence.
CMOS Digital Design -- FPGA Application Design -- ASIC Design -- Analog and Mixed Signal Design.
Keywords: Engineering; Engineering; PROCESSOR ARCHITECTURES; ELECTRONICS AND MICROELECTRONICS, INDTRUMENTATION; CIRCUITS AND SYSTEMS; ELECTRONICS; SYSTEMS ENGINEERING; COMPUTER SCIENCE